2018
DOI: 10.1364/oe.26.009615
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the reflectance coefficient of skylight from the ocean surface and its implications to ocean color

Abstract: The value and spectral dependence of the reflectance coefficient (ρ) of skylight from wind-roughened ocean surfaces is critical for determining accurate water leaving radiance and remote sensing reflectances from shipborne, AERONET-Ocean Color and satellite observations. Using a vector radiative transfer code, spectra of the reflectance coefficient and corresponding radiances near the ocean surface and at the top of the atmosphere (TOA) are simulated for a broad range of parameters including flat and windy oce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Glint, a common issue for L8 and S2, could contribute additional scattered light to the satellite-observed signal and is currently not corrected for over turbid waters by most standard approaches. Glintremoval methods are predominantly developed for clear-water marine systems yet can profoundly influence R rs estimates (Gilerson et al, 2018). For water retrievals, glint corrections can cause up to 43% MAPD in R rs , significantly impacting the resulting Chl-a retrievals (Garaba et al, 2015).…”
Section: Validation Of Remote Sensing Reflectancementioning
confidence: 99%
“…Glint, a common issue for L8 and S2, could contribute additional scattered light to the satellite-observed signal and is currently not corrected for over turbid waters by most standard approaches. Glintremoval methods are predominantly developed for clear-water marine systems yet can profoundly influence R rs estimates (Gilerson et al, 2018). For water retrievals, glint corrections can cause up to 43% MAPD in R rs , significantly impacting the resulting Chl-a retrievals (Garaba et al, 2015).…”
Section: Validation Of Remote Sensing Reflectancementioning
confidence: 99%
“…The calculated error budget showed that the iterative model used in the atmospheric correction algorithm of OLCI has a smaller impact on the error of R rs compared to the NASA iterative model used to process the MODIS and VIIRS data over the open ocean around China. The main influencing factors on the error of R rs for OLCI, MODIS, and VIIRS are the aerosol LUTs and the Rayleigh-corrected radiance (the error of system vicarious calibration, the error of Rayleigh scattering, whitecaps, gas and glint correction algorithm, and surface effects [51,66]) used in the atmospheric correction algorithm over the open ocean and coastal waters around the China Sea.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this threshold, 18 stations were removed. The surface-reflected radiance (mainly due to sky glint because direct sun glint is usually weak with measurement geometry) is recognized as a major sources of uncertainty [50,51]; thus, a station The surface-reflected radiance (mainly due to sky glint because direct sun glint is usually weak with measurement geometry) is recognized as a major sources of uncertainty [50,51]; thus, a station was discarded when the ρL sky /L t exceeded 50%, [50,52]. Based on this threshold, eight stations were removed.…”
Section: Consistency Of Multiple Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…where ρ (Equation (2)) (defined as the ratio of the surface-reflected radiance at the specular direction corresponding to the downwelling sky radiance from one direction) is the water-surface reflected factor used to correct the surface radiance reflection or glint effect-one of the main constraints of above-water measurements [9]. The ρ values depend on the viewing geometry of the sensor, environmental conditions (incident irradiance, solar zenith angle-SZA, wind speed), and atmospheric composition (aerosol, molecules, cloud coverage) [7,10,11]. Besides, the more accurate estimate of ρ, the more accurate are the R rs datasets for atmospheric correction validations, vicarious calibration of sensors, and bio-optical models [5,12].…”
Section: Introductionmentioning
confidence: 99%